Incentives for Supply Adequacy in Electricity Markets. An Application to the Mexican Power Sector - Víctor G. Carreón-Rodríguez; Juan Rosellón (Centro de Investigación y Docencia Económicas, A.C., 2009)
This paper studies resource adequacy, i.e. the market design dilemma of ensuring enough generation capacity in the long run. International experiences have shown that it is difficult that the market alone provides incentives to attract enough investment in capacity reserves. We analyze various measures to cope with this problem, including moth-ball reserves, capacity payments, icap and call options. We then construct a model to analyze the structure of incentives for the expansion of electricity supply in the spot market, and capacity in the long run electricity reserve market. Through a game-theory model, we analyze price convergence in three markets: the peak spot market, the non-peak spot market, and the long-run capacity reserve market. We finally carry out a simulation for Mexican power generation. The combination of cfe´s virtual market, together with capacity payments, has eventually resulted in capacity generation expansion similar to what would be attained in an open electricity market, such as the one modelled in our study. But this does not necessarily imply that the Mexican electricity industry will not need in the future -if the generation market is fully open to private investment- some of the discussed capacity incentive mechanisms.